Green extraction of puromycin-based antibiotics from Streptomyces albofaciens (MS38) for sustainable biopharmaceutical applications - Singh, Neha; Patil, Sandip; Shahnawaz, Mohd.; Rai, Vibhuti; Patil, Abhinandan; Tripathi, C. K. M.; Wen, Feiqiu; Dong, Shaowei; Cai, Defeng (Frontiers in Chemistry, 2024)
Background: Microbial secondary metabolites have shown promise as a source of novel antimicrobial agents. In this study, we aimed to isolate, characterize, and evaluate the antimicrobial activity of compound from a novel Streptomyces albofaciens strain MS38. The objective was to identify a potential bioactive compound with broad-spectrum antimicrobial properties. Methods: The isolated strain MS38 on starch casein agar was characterized using morphological, physiological, and molecular identification techniques. The compound was obtained from the fermented broth through extraction with n-butanol and further purification using silica gel column chromatography and high-performance liquid chromatography (HPLC). Structural elucidation was conducted using Ultraviolet (UV), Infrared (IR), nuclear magnetic resonance (NMR), and mass spectrometry (MS) techniques. The antimicrobial activity was evaluated using the agar well diffusion method and the microplate Alamar blue assay (MABA). Results: The isolated strain MS38 was identified as novel Streptomyces albofaciens based on morphological characteristics and confirmed by 16S sequences analysis and MALDI-TOF MS. The compound obtained from the fermented broth exhibited substantial antimicrobial activity against a variety of pathogenic bacteria and fungi. Structural analysis revealed a complex chemical structure with characteristic functional groups indicative of potential antimicrobial properties. The compound demonstrated strong activity against both Gram-positive (Staphylococcus Spp.) and Gram-negative (Klebsiella pneumoniae and Escherichia coli) bacteria, as well as fungi, including Candida albicans and Trichophyton rubrum. Conclusion: This study successfully isolated and characterized a bioactive compound from a novel Streptomyces albofaciens MS38. The compound exhibited significant antimicrobial activity against a range of pathogenic microorganisms. These findings underscore the importance of exploring microbial biodiversity for the discovery of novel antimicrobial agents. This study contributes to the growing knowledge of microbial secondary metabolites with potential therapeutic value.